MORPHOFUNCTIONAL CHARACTERISTICS OF THE SMALL INTESTINE DURING EXPERIMENTAL CHOLECYSTECTOMY AND ANTIHYPOXANT THERAPY IN ACUTE SMALL INTESTINAL OBSTRUCTION (Journal of Universal Science Research, 2023)
This article discusses the morphofunctional characteristics of the small intestine, cholecystectomy in the small intestine. It also provides information on antihypoxant therapy of the small intestine with examples.